1981
DOI: 10.1073/pnas.78.4.2053
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sites on prostaglandin cyclooxygenase are determinants in the action of nonsteroidal antiinflammatory agents.

Abstract: Evidence is presented to show that nonsteroidal antiinflammatory drugs react with two sites on the cyclooxygenase (8,11,14-eicosatrienoate, hydrogen-donor:oxygen oxidoreductase, EC 1.14.99.1). Although the degree of interaction with the catalytic site determines the potency of such compounds, interaction with the supplementary site is also obligatory for efficacy as cyclooxygenase inhibitors and may explain the selectivity of such drugs in inhibiting the cyclooxygenase but not the lipoxygenase pathway. Drugs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
2

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 16 publications
2
33
2
Order By: Relevance
“…4D). This is comparable with the effect aspirin has on PGHS, where covalent acetylation of the protein occurs within 15 min of exposure to aspirin (31)(32)(33) and suggests that the irreversible inhibition observed with AOS might also be because of a covalent modification. To test this, quantities of purified AOS were incubated with 14 C-acetate-labeled aspirin for 1 or 2 h. AOS was then precipitated, repeatedly washed, and subjected to SDS-PAGE autoradiography.…”
Section: Resultssupporting
confidence: 57%
“…4D). This is comparable with the effect aspirin has on PGHS, where covalent acetylation of the protein occurs within 15 min of exposure to aspirin (31)(32)(33) and suggests that the irreversible inhibition observed with AOS might also be because of a covalent modification. To test this, quantities of purified AOS were incubated with 14 C-acetate-labeled aspirin for 1 or 2 h. AOS was then precipitated, repeatedly washed, and subjected to SDS-PAGE autoradiography.…”
Section: Resultssupporting
confidence: 57%
“…Although salicylate has been shown to be similarly potent as an analgesic and anti-inflammatory drug (Atkinson & Collier, 1980; Rainsford, 1984), it has almost no effect on prostanoid formation of gastric mucosa (Ligumsky et al, 1982;Whittle et al, 1980), macrophages (Kuehl et al, 1980), ram seminal vesicle microsomes (Humes et al, 1981), or thrombocytes (Roberts et al, 1984;Smith & Willis, 1971;Vargaftig, 1978a). Platelet function is not affected by salicylate as well (O'Brien, 1968;Roberts et al, 1984;Smith & Willis, 1971;Weiss et al, 1968;Zucker & Peterson, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Surveying our results and the data provided by Kuehl et al (1981) and Humes et al (1981) we suppose that cyclo-oxygenases as well as lipoxygenases contain additional, perhaps rather similar, supplementary binding sites in addition to the wellrecognized, rather different, catalytic sites. In such a model the pattern of interaction with both sites determines the final pharmacological profile of an individual agent resulting in either selective inhibition of cyclo-oxygenases, lipoxygenases or of both enzymes.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Kuehl et al (1981) and Humes et al (1981) demonstrated that certain analgesicantipyretic agents apparently interact with two sites on the cyclo-oxygenase. The interaction of these inhibitors with the proposed supplementary binding site was suggested to explain the interactions of weak and potent cyclo-oxygenase inhibitors: drugs interacting more effectively with the supplementary site, which is obligatory for inhibitory action, than with the catalytic site, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation